Hubungan Hipertensi Terhadap Kematian Pasien Covid-19 Dengan Diabetes Melitus Tipe 2 di RSUP dr. Sardjito - Fadhilah, Farah; Susanti, Vina Yanti; Nugroho, Dhite Bayu; Adhikara, Imam Manggalya; Handajani, Fitri (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2024)
Diabetes mellitus and hypertension are co-morbidities that are often found in COVID-19 patients. Diabetes can reduce the body's immunity and increase the rate of viral replication, and is associated with vascular problems. Hypertension is one of the comorbid diabetes with high morbidity and mortality. To determine the relationship between hypertension and the death of COVID-19 patients with type 2 diabetes mellitus at Dr Sardjito General Hospital. Observational study with a retrospective cohort study design, using COVID-19 registry data at Dr Sardjito General Hospital for the period March 2020-July 2021. COVID-19 patients with type 2 diabetes mellitus who had hypertension and those who did not have hypertension were selected at Dr Sardjito General Hospital and Collected data on mortality, age, sex, other comorbidities, severity and length of stay. Data were processed using SPSS, in univariate, bivariate, and multivariate analysis models. the results of multivariate analysis using logistic regression found that hypertension, age, and ischemic heart disease did not have a significant association with the death of COVID-19 patients with type 2 diabetes mellitus. The variable that had the greatest power as a predictor of death in COVID-19 patients with diabetes mellitus type 2 is ARDS with a risk of death 20.8 times higher than without ARDS. Patients with kidney failure are at risk of dying 2.7 times higher than those without kidney failure. The addition of length of stay (LOS) 1 day of treatment reduces the risk of death by 16.3%. Hypertension has no significant relationship as a predictor of death in COVID-19 patients with type 2 diabetes mellitus at Dr Sardjito General Hospital. Significant predictors of death in this study were ARDS, kidney failure, and were associated with length of stay (LOS).